Mammalian Mitochondrial Ribonuclcates - Bartoov, Benjamin (My University, 1971)
Mitochondria from mammalian cells synthesize protein. To characterize this sytem, high molecular weight RNA and ribosomal components from mitochondria of rat, mouse and human sources were investigated. Novel ribosomal RNA and ribosomal components were found in these organisms which are unique compared with their counterparts in the cytoplasm or bacteria in respect to their physical properties, chemical composition and conformation. The RNA sedimentation cofficients of 15 and 13 S, electrophoretic mobilities of about 21 and 12.5 SE and 20.5 and 11.0 SE for rodent and human cells respectively, and a high A+U content. The mitochondrial ribosomal RNA was transcribed from the mitochondria originated from an autonomous prokaryotic ancestor whic established a symbiotic relationship in the contemporary eukaryotic cell in which the original prokaryotic symbiont lost part of its autonomy.
Department title for this thesis is Molecular Biology, which is not listed in the categories.
Keywords: mammals; cells; mitochondria; rat; mouse; human; Biochemistry, Biophysics, and Structural Biology; Life Sciences; Molecular Biology; Biochemistry, Biophysics, and Structural Biology